KINERJA SISTIM HIDROLIK PADA UNIT EXCAVATOR 320D2 CATERPILLAR - Halim , Abdul; Fadli , Ma’arif; Mangkona , Mangkona (Jurnal Rekayasa Mesin, 2024)
Almost most heavy equipment units use a hydraulic system, including systems that are important for heavy equipment units to work. The hydraulic performance test on the excavator unit is part of the test carried out as an operational standard to state that the unit is good to run or operate in work in the field. So to know that the unit has good availability, it is necessary to carry out regular testing according to service guidelines. This research aims to provide information regarding standard operational procedures for testing hydraulic excavator performance, both cycle time and pressure on directional control valves. The method used is to carry out tests on hydraulic implements using a combination of system information services. In experimental testing, the cycle time for the movement of hydraulic implements, including boom, bucket, stick, swing, and travel, still complies with standard specifications. For testing, pilot relief valve pressure, main relief valve pressure, and swing pressure are all still within normal standard limits.